Antipodal Vivaldi Antenna to Detect UHF Signals That Leaked Out of the Joint of a Transformer - Jian Zhang; Xiaoxing Zhang; Song Xiao (International Journal of Antennas and Propagation)
In recent years, extensive research has been conducted on the ultrahigh-frequency (UHF) method. Considering that acquiring a partial discharge UHF signal is the first step in a series of tasks, such as fault diagnosis and defect location, the UHF sensor plays an important role in the UHF method. An antipodal Vivaldi antenna installed at a transformer’s joint is designed in this study according to the structural features of 750 kV transformers in China. Several effective structures, such as linear gradient microstrip and slot edge, are employed to improve the return loss and radiation characteristics. A metal box is designed after analyzing the influence of the metal around the antenna. The metal box can effectively shield against electromagnetic interference and does not deteriorate the performance of the antenna significantly. Experimental data show that this antenna is much more sensitive than the rectangular plane spiral antenna. The proposed antipodal Vivaldi antenna is suitable for detecting partial discharge in large transformers.